Die sozioökonomischen Auswirkungen nationalsozialistischer Arbeitseinsatz- und Frauenpolitik in Tirol - Hester Margreiter (Historia.scribere)
Abstract Social and economic impacts of Nazi women’s labor policy in Tyrol The ambivalence of Nazi ideology between denigration of women as second class citizens and propagandist idealization as a mothers and housewives allows for a variety of subjective and objectified patterns of interpretation in connection with the targeted embedding of women in the labor and employment process. The importance of women and their opportunities in society in terms of theoretical versus practical classification in the reproductive and employment process allows conflicting interpretations. Women were subject to the constraint to production and reproduction, but some of them could also find self-realization and new freedoms in the working duty. The background of this ambivalence and their theoretical, economic and social impacts will be studied in the present work.